Genetic Removal of the CH1 Exon Enables the Production of Heavy Chain-Only IgG in Mice - Zhang, Tianyi; Cheng, Xueqian; Yu, Di; Lin, Fuyu; Hou, Ning; Cheng, Xuan; Hao, Shanshan; Wei, Jingjing; Ma, Li; Fu, Yanbin; Ma, Yonghe; Ren, Liming; et al. (Frontiers in Immunology, 2018)
Nano-antibodies possess great potential in many applications. However, they are naturally derived from heavy chain-only antibodies (HcAbs), which lack light chains and the CH1 domain and are only found in camelids and sharks. In this study, we investigated whether the precise genetic removal of the CH1 exon of the γ1 gene enabled the production of a functional heavy chain-only IgG1 in mice. IgG1 heavy chain dimers lacking associated light chains were detected in the sera of the genetically modified mice. However, the genetic modification led to decreased expression of IgG1 but increased expression of other IgG subclasses. The genetically modified mice showed a weaker immune response to specific antigens compared with wild type mice. Using a phage-display approach, antigen-specific, single domain VH antibodies could be screened from the mice but exhibited much weaker antigen binding affinity than the conventional monoclonal antibodies. Although the strategy was only partially successful, this study confirms the feasibility of producing desirable nano-bodies with appropriate genetic modifications in mice.